1997
DOI: 10.1021/ja972191k
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Zr-Catalyzed Carbomagnesation and Mo-Catalyzed Macrocyclic Ring Closing Metathesis in Asymmetric Synthesis. Enantioselective Total Synthesis of Sch 38516 (Fluvirucin B1)

Abstract: The first enantioselective total synthesis of antifungal agent Sch 38516, also known as fluvirucin B1, is described. The synthesis includes a convergent asymmetric preparation of amine 17 and acid 18, which are then united to afford diene 62. Metal-catalyzed transformations play a crucial role in the synthesis of the latter moiety. Of particular note are the diastereo- and enantioselective Zr-catalyzed alkylations, a tandem Ti- and Ni-catalyzed process that constitutes a hydrovinylation reaction, and a Ru-cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 69 publications
1
77
0
4
Order By: Relevance
“…19) However, the former resulted in decomposition and the latter proceeded slowly. Thus, the oxidation was carried out in 2 steps to achieve more suitable conditions; the reactions of 18-a and 19-a with a combination of TPAP and N-methylmorpholine-N-oxide (NMO) in CH2Cl2 provided intermediate aldehydes, and their further oxidation with sodium chlorite in the presence of 2-methyl-2-butene led to carboxylic acids 21 and 22 in respective 64.4z and 70.2z yields.…”
Section: )mentioning
confidence: 99%
“…19) However, the former resulted in decomposition and the latter proceeded slowly. Thus, the oxidation was carried out in 2 steps to achieve more suitable conditions; the reactions of 18-a and 19-a with a combination of TPAP and N-methylmorpholine-N-oxide (NMO) in CH2Cl2 provided intermediate aldehydes, and their further oxidation with sodium chlorite in the presence of 2-methyl-2-butene led to carboxylic acids 21 and 22 in respective 64.4z and 70.2z yields.…”
Section: )mentioning
confidence: 99%
“…Generally, the reversible nature of this sequential process is responsible for the thermodynamic control of the metathesis product. [12] Thus, in principle, the stereochemical outcome of the RCM reaction to form macrocycles will be governed by the thermal stabilities of the corresponding E and Z isomers, and a thermodynamic distribution of the products will be achieved after sufficient reaction time. Although this may imply that the same substrate will always produce a settled ratio of the E/Z mixture regardless of the class of RCM initiator, there have been a number of examples in which the structure of the RCM initiator affected the E/Z selectivity of the macrocyclic products.…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in the understanding of the function of various ligands on RCM catalysts have provided insight into the factors controlling E/Z selectivity for macrocyclic-olefin formation. [11][12][13][14][15] In particular, DFT-calculation studies have suggested the energy levels of intermediates in olefin-metathesis catalytic cycles, including those with firstand second-generation ruthenium complexes. [16] To explain our experimental results, we would like to set forth a hypothesis that the energy level of the intermediate ruthenacyclobutane is higher than that of olefin-ruthenium p complex in the case of bisphosphane-type catalysts, but lower in the case of NHC-containing catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…29 Several examples of natural products synthesized in the last few years that involve one or more olefin metathesis steps are Epothilone C, 30 metathesis catalysts best achieves each of the metathesis reactions is determined through screening procedures, and trends are beginning to emerge. Newer catalysts, e.g., Lewis acid activated 33 or high oxidation state complexes that contain an NHC ligand, 34 have not yet been examined to any significant degree as catalysts for various types of metathesis reactions.…”
Section: Organic Synthesismentioning
confidence: 99%